The feather mites of the hoatzin Opisthocomus hoazin (Muller) (Aves: Opisthocomiformes), with the description of two new genera and six new species (Acari: Analgoidea, Pterolichoidea) - Hernandes, Fabio A. [UNESP]; Mironov, Sergey V. (Magnolia Press, 2015)
Six new species and two new genera of feather mites are described from the hoatzin Opisthocomus hoazin (Muller) (Opisthocomiformes: Opisthocomidae) in Brazil: Gymnolichus lacrimosus sp. n., G. latihumeralis sp. n. (Xolalgidae), Temnalges hoazin sp. n., T. atelodiscus sp. n. (Psoroptoididae), Ciganalichus boasfilhoi gen. n., sp. n., and Hoazinacarus anisosetus gen. n., sp. n. (Pterolichidae). Illustrations of two previously known species, Opisthocomacarus umbellifer (Trouessart, 1899) and Stakyonemus hystrix (Trouessart, 1899) are provided. We show that the hoatzin bears a much richer feather mite fauna than previously thought and presently includes eight mite species from three families: Xolalgidae, Psoroptoididae (Analgoidea) and Pterolichidae (Pterolichoidea). They represent two morpho-ecological groups: (1) mites inhabiting the wing and tail feathers, and (2) mites living in downy and body contour feathers. We hypothesize that these mites represent a native feather mite fauna of the hoatzin, inherited from its ancestors and existing on this bird for a long time. The controversial and unresolved relationships of this bird with other bird taxa are briefly discussed in the light of the new acarofauna discovered.
Keywords: feather mites; taxonomy; biodiversity; Neotropical region; new genera; new species